Main advantages of flat matrix granulators - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (My University, 2021)
An important element in the development of modern recycling of secondary materials is the choice of a rational method of compaction of raw materials, as well as the improvement, introduction of methods for their effective granulation, which, together with a significant decrease in volume, will allow maintaining the high quality of pressing bulk materials.
Keywords: development of modern recycling; rational method of compaction of raw materials; production of granulated feed; granules; agricultural waste